It will be very helpful once I understand ATLAS.ti": Teaching ATLAS.ti using the Five-Level QDA method. Issue 1 (2nd January 2019) - Paulus, Trena M.; Pope, Elizabeth M.; Woolf, Nicholas; Silver, Christina
ABSTRACT: Few studies have explored approaches to teaching qualitative data analysis software (QDAS). As more researchers rely on self-teaching, more research into best practices for developing QDAS expertise is warranted. In this paper, we report our experience using the Five-Level QDA® method to guide the design of an introductory ATLAS.ti workshop. By focusing on the translation process between analytic strategies and the tactics of the software, we sought to help students harness ATLAS.ti powerfully. Using a case study and reflective practice approach, we reviewed instructional materials, observational field notes, instructor reflections, student questionnaires, and interviews to describe what happened during the workshop as well as instructor and learner perceptions of the method. For the method to be successful, methodological competence prior to training and ongoing support after training are necessary, both of which may be fostered by using community-building strategies during and after instruction. Hands-on exploration of the software components during the workshop, including demonstration of both in-progress and completed projects by the instructor and peers, can bring life to the Five-Level QDA method. While the method emphasizes that powerful use of the software requires analytic strategies to drive software tactics, learners may view the two as mutually constituting. Implications for teaching QDAS as well as the development of the Five-Level QDA method are explored.